Error Detecting Dual Basis Bit Parallel Systolic Multiplication Architecture over GF(2m) - Singh, Ashutosh Kumar; Bera, A.; Rahaman, H.; Mathew, J.; Pradhan, D. (University of Electronic Science and Technology, 2009)
An error tolerant hardware efficient very large scale integration (VLSI) architecture for bit parallel systolic multiplication over dual base, which can be pipelined, is presented. Since this architecture has the features of regularity, modularity and unidirectional data flow, this structure is well suited to VLSI implementations. The length of the largest delay path and area of this architecture are less compared to the bit parallel systolic multiplication architectures reported earlier. The architecture is implemented using Austria Micro System's 0.35 m CMOS (complementary metal oxide semiconductor) technology. This architecture can also operate over both the dual-base and polynomial base.